Kekerasan dan Abortus Provocatus - Tarigan, Jacobus (Jurnal Etika Respons, 2009)
Abortus provocatus is one of the sadistic violent actions that make the fetus as its scapegoat and the victim of Â violence. It is a criminal action that breaks the law and the moral values. As many other violence actions that is inherited genetically and socially in human society, abortus provocatus endangers human life and its enviroment. To prevent this violent action this article suggests that we need education on love and the creation of love culture.